Mechanism of the Formation of Electronically Excited Species by Oxidative Metabolic Processes: Role of Reactive Oxygen Species - Pospíšil, Pavel; Prasad, Ankush; Rác, Marek (Biomolecules, 2019)
It is well known that biological systems, such as microorganisms, plants, and animals, including human beings, form spontaneous electronically excited species through oxidative metabolic processes. Though the mechanism responsible for the formation of electronically excited species is still not clearly understood, several lines of evidence suggest that reactive oxygen species (ROS) are involved in the formation of electronically excited species. This review attempts to describe the role of ROS in the formation of electronically excited species during oxidative metabolic processes. Briefly, the oxidation of biomolecules, such as lipids, proteins, and nucleic acids by ROS initiates a cascade of reactions that leads to the formation of triplet excited carbonyls formed by the decomposition of cyclic (1,2-dioxetane) and linear (tetroxide) high-energy intermediates. When chromophores are in proximity to triplet excited carbonyls, the triplet-singlet and triplet-triplet energy transfers from triplet excited carbonyls to chromophores result in the formation of singlet and triplet excited chromophores, respectively. Alternatively, when molecular oxygen is present, the triplet-singlet energy transfer from triplet excited carbonyls to molecular oxygen initiates the formation of singlet oxygen. Understanding the mechanism of the formation of electronically excited species allows us to use electronically excited species as a marker for oxidative metabolic processes in cells.
Keywords: Oxygen; reaktivní formy kyslíku; superoxide anion radical; Energy Transfer; přenos energie; hydrogen peroxide; oxidace-redukce; Reactive Oxygen Species; electronically excited species; oxidative radical reactions; Animals; kyslík; lidé; hydroxyl radical; Humans; singlet oxygen; zvířata; chromophores; Oxidation-Reduction; reactive oxygen species